Exploring How Extracurricular Activities Shape Diversity Management in Ethiopian Public Higher Education - Dr. Easaw Alemayehu Assefa (The Journal of Quality in Education)
This paper explores the role of co-curricular activities in managing diversity within Ethiopia's public higher education institutions (HEIs). It aims to identify the challenges these institutions face in promoting diversity through extracurricular initiatives while examining faculty and student perceptions regarding their effectiveness. A mixed-method research approach was employed, involving a quantitative survey of 350 respondents, evenly split between males and females, and a qualitative component featuring 10 purposefully selected participants. Data were gathered through questionnaires and interviews. The findings shed light on the perspectives of students and faculty on managing diversity through extracurricular activities, highlighting the challenges faced by Ethiopian HEIs in leveraging these initiatives for diversification. Additionally, the study identifies various settings within these institutions that can support diversity management through organized activities. This research contributes to the existing literature on the significance of extracurricular activities in diversity management in Ethiopian public HEIs. It offers insights into the attitudes, concerns, and potential of implementing diversity through out-of-class activities. The study concludes with recommendations for directing diversity-focused co-curricular activities, improving the environment for underrepresented groups, and creating facilities that facilitate their participation in extracurricular programs.